Lidocaine- and chloramphenicol-loaded nanoparticles embedded in a chitosan/hyaluronic acid/glycerol matrix: Drug-eluting biomembranes with potential for guided tissue regeneration - Vasconcelos, Mariana Oliveira; Silva, Luís Antônio Dantas; Sousa-Junior, Ailton Antonio; dos Santos, Thaís Rosa Marques; da Silva, Carla Afonso; Valadares, Marize Campos; Lima, Eliana Martins (Frontiers in Nanotechnology, 2022)
Guided tissue regeneration (GTR) is a dentistry technique based on the use of polymeric biomembranes as physical barriers for selective cell exclusion, directing the growth of gingival tissue, bone tissue, and periodontal ligaments in a region previously affected by periodontitis. Postoperative pain and microbial infection constitute, however, two major challenges to be tackled right after implantation. To address these challenges, we prepared and characterized eight chitosan/hyaluronic acid/glycerol (CS/HA/GL) bioresorbable membranes embedded with lidocaine- and chloramphenicol-loaded polycaprolactone nanoparticles (LDNP and CHNP, respectively), combining the local anesthetic effects of lidocaine with the antibacterial effects of chloramphenicol. The formulations were prepared with varying amounts of CS, HA, GL, LDNP, and CHNP. As a plasticizing agent, GL could modulate the samples mechanical properties such as thickness, morphology, tensile strength, elongation at break, as well as swelling and degradation in simulated saliva. Two samples exhibited greater resistance to biodegradation and were selected for further studies. Their drug release profiles indicated that LDNP and CHNP first detach from the membrane matrix, and a zeroth order drug release kinetics from the detached NPs dominates the overall process thereafter, with lidocaine being released 3 times faster than chloramphenicol, in a controlled and sustained rate over time. Drug encapsulation efficiency was such that optimal samples exhibited bactericidal activity (inhibition halos) against gram-positive S. aureus and gram-negative A. actinomycetemcomitans strains similar to that observed for free chloramphenicol. Finally, one of these samples showed no intrinsic toxicity against healthy mammalian model cells (99% viability for the unloaded membrane; 80% viability for the fully LDNP- and CHNP-loaded membrane), and may now be further optimized as a drug-eluting biomembrane with potential for GTR.